PENGGUNAAN ABU MERANG PADI (Oryza Sativa) UNTUK PENGOLAHAN SNACK CUMI-CUMI (Loligo sp) ASAP YANG DISIMPAN SECARA VAKUM - Dahlia, Dahlia; Pulungan, Afran Rouzami (Jurnal Perikanan dan Kelautan, 2011)
Research of squid (loligo sp) snack using rice straw ashes A1=0%, A2=0,5%and A3=1,0% and storage with vacuum method for 0 day, 5 day, 10 days and 15days. This research to evaluate the application of rice straw ashes as softenermaterial or blooming of smoked squid and quality of smoked squid snackobserved from organoleptic quality (appearance, smell, taste, texture) watercontent, protein content, lipid and peroxide.Concentraci of rice straw ashes is different a significant in value, smell,texture, water content, protein content and lipid content (P<0,01). The treatmentsis not different value and peroxide content (P>0,05). The appearance and smell A1is better than A2, and A2 is better than A3. Texture value, water content, proteincontent, and lipid A3 is better than A2 and A2 better than A1. But for taste valueand peroxide content there’s no different in every treatment.Rice straw ashes can used for softening the smoked squid and make textureof smoked squid snake can be delicious and crispy. The treatment A3 (1,0%) is thebest in this research.